Penerapan Metode Role Playing Pada Mata Pelajaran Bahasa Indonesia Untuk Meningkatkan Hasil Belajar Siswa - Erlin; Alfan Nurngain (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
The aim of this research is to determine the application of the role playing learning method to improve Indonesian language learning outcomes for Class VI students at SD and to find out what obstacles there are in implementing the role playing learning method in improving Indonesian language learning outcomes for Class VI students at SD. . This research uses a qualitative descriptive method to describe the application of the role playing method in Indonesian language subjects to improve the learning outcomes of Class VI students at SD. The sample in this study was only 1 class VI homeroom teacher. The use of the Role Playing learning method can increase the active learning outcomes of class VI students at SD Negeri 1 Kalikarung. The following data shows student learning outcomes. Based on data from the learning outcomes of 30 students, the average use of the roller playing method for students has increased. The suggestions that researchers can convey are that teachers can use role playing in learning, because role playing can increase teacher activity and student activity in learning Indonesian; 2. Teachers should use role playing, because using role playing can improve students' Indonesian language learning outcomes; 3. Teachers can use role playing to help improve students' Indonesian language learning outcomes.